Cross-Species Metabolic Profiling of Floral Specialized Metabolism Facilitates Understanding of Evolutional Aspects of Metabolism Among Brassicaceae Species - Liu, Yuting; Watanabe, Mutsumi; Yasukawa, Sayuri; Kawamura, Yuriko; Aneklaphakij, Chaiwat; Fernie, Alisdair R.; Tohge, Takayuki (Frontiers in Plant Science, 2021)
Plants produce a variety of floral specialized (secondary) metabolites with roles in several physiological functions including light-protection, attraction of pollinators and protection against herbivores. Pigments and volatiles synthesized in the petal have been focused on and characterized as major chemical factors influencing pollination. Recent advances in plant metabolomics have revealed that the major floral specialized metabolites found in land plant species are hydroxycinnamates, phenolamines and flavonoids albeit these are present in various quantities and encompass diverse chemical structures in different species. Here, we analyzed numerous floral specialized metabolites in twenty different Brassicaceae genotypes encompassing both different species and in the case of crop species different cultivars including self-compatible and self-incompatible species by liquid chromatography-mass spectrometry (LC-MS). Of the 228 metabolites detected in flowers among twenty Brassicaceae species, fifteen metabolite peaks including four phenylacyl-flavonoids and two phenolamides were detected and annotated as key metabolites to distinguish self-compatible and self-incompatible plant species, respectively. Our results provide a family-wide metabolic framework and delineate signatures for compatible and incompatible genotypes thereby providing insight into evolutionary aspects of floral metabolism in Brassicaceae species.